Emotion Regulation in View of Gender in Students Who Study While Working - Napitupulu, Andiny Christy; Simatupang, Elsa Manora; Siagian, Novel; Purba, Putri Regina Margaretha; Mirza, Rina (IAIN Kudus, 2024)
Emotion Regulation in View of Gender in College Students Who Study While Working. This study aims to see if there are differences between emotion regulation in male and female students who study while working. The sample of this study were 95 students (41 male students and 54 female students) who worked while studying with an age range of 18-41 years, from the Faculty of Psychology, Prima Indonesia University, using the snowball sampling technique. With this limited number, the entire population was used as a sample in this study or also known as total sampling. Emotion Regulation Scale as a container for data accumulation in this study which is the result of the adaptation of the ERQ (Emotion Regulation Questionaire) questionnaire with t> 1.96; p = 0.000. The results of the study using Independent Sample T-Test with a significance value of 0.325 (p> 0.05) which shows that the hypothesis is rejected, in the sense that there are no differences in emotional regulation between male students and female students who study while working. Keywords: Emotion Regulation, Working Students, Gender